ANALISIS HASIL ANGKET KEBUTUHAN PESERTA DIDIK (AKPD) UNTUK MENENTUKAN TOPIK LAYANAN BIMBINGAN KLASIKAL PADA KELAS X-I DI SMA NEGERI 1 SELONG - Zamdi, Pathul; Suhartiwi, Suhartiwi; Takiuddin, Muhamad (Universitas Hamzanwadi, 2024)
Guidance and counseling services are an effort to help students in developing their personal lives, social lives, learning activities, as well as career planning and development. This research aims to analyze all the needs of class X-I students at SMAN 1 Selong in all areas of counseling services (Personal, Social, Learning, Career) to determine the topic of classical guidance services. This research method uses quantitative and survey with data collection techniques using a student needs questionnaire (AKPD). This research uses a saturated sample or the entire population is a sample, namely 36 students in class X-1. The research results show that students have needs in the field of personal services (30.00%), the field of social (20.66%), the field of learning (35.66%), and career (13.68%). So the topics used in the Classical Tutoring Service in the Learning Sector are